Ultrasound, Computed Tomography, and Magnetic Resonance Imaging in a Patient With Medullary Cystic Kidney Disease. Issue 4 (December 2018) - Whang, Gilbert; Tchelepi, Hisham
Abstract : Abstract: Among the renal cystic diseases that result in end-stage renal disease, an important hereditary cause is medullary cystic kidney disease, which affects adults in an autosomal dominant pattern. It is characterized by progressive renal failure, tubulointerstitial fibrosis, and formation of small cysts in the renal medulla and corticomedullary junction. While the appearance of medullary/corticomedullary cysts may not be pathognomonic for medullary cystic kidney disease, encountering a patient with renal failure and medullary/corticomedullary cysts should prompt further investigation, given the implication of having the disease. Genetic testing can be used to identify potential renal donors as well as identify affected individuals in order to control risk factors for chronic renal disease that may mitigate the progression of the disease process. The treatment of choice is renal transplantation.